The role of strategic intelligence dimensions in achieving the requirements of entrepreneurial success: A survey of the opinions of managers of a group of commercial companies in Duhok Governorate - عمر, محمد عبد الرحمن; محمد, روش ابراهيم (Sulaimani Journal for Humanities, 2019)
The current research aims to identify the role of strategic intelligence dimensions in achieving the requirements of entrepreneur success in a number of commercial companies operating in Dohuk Governorate. Strategic intelligence is one of the most important contemporary issues in the field of strategic management that can be used by the organization in formulating its strategies. It also considers entrepreneur success as one of the modern topics in the entrepreneur thinking and important factors that help the organization to achieve growth and continuity and stay in the market. The research hypothesizes that there is a correlation and influence of strategic intelligence in achieving entrepreneur success. In order to achieve the objectives of the research, the questionnaire was used as a basic tool in collecting data and information from researched individuals, the research sample was selected from (45) managers and assistants in a number of commercial companies in order to achieve the desired results.The statistical analysis of the research (SPSS-22) was used to conduct the statistical analysis of the research, several descriptive statistical methods were used, such as Pearson correlation coefficient, linear regression coefficient, T test, F test, in order to analyze the data to identify the nature of the relationship of correlation and influence between independent and approved variables. The results of the analysis showed the following: The results of the analysis showed that all the dimensions of strategic intelligence, such as prospecting, organized thinking, vision, motivation, partnership, are available to managers of the surveyed companies, indicating the efficiency required to achieve the entrepreneur success. One of the most important proposals has been to emphasize the spread of strategic intelligence throughout the organization and to try to make it part of its culture by engaging individuals in training courses because of the potential to employ strategic intelligence to achieve entrepreneur success.
Keywords: strategic intelligence; strategic intelligence dimensions; entrepreneur success; success; entrepreneur success requirements